IMPLEMENTASI 5S (SEIRI, SEITON, SEISO, SEIKETSU DAN SHITSUKE) TERHADAP PRODUKTIVITAS KERJA PADA PT. EKAPUTRA PRADA INDONESIA DI PEKANBARU - ,Anggia Paramitha, Ryan Sury Febriansyah Simatupang ,Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The company is a management function and a collection of people involved in an activity to achieve a predetermined goal. In practice, companies need resources to carry out business activities. One of the resources needed to manage the business activities of a company is human resources (HR). Human resources have a very important role because without this element the company will not be able to achieve the goals that have been set. Work productivity will be very important in improving company performance, this is because work productivity is a measure of the quality and quantity of a workforce in a unit of time to achieve results. or work performance effectively and efficiently with the resources used. This study aims to see and determine the direct effect of 5S implementation on work productivity. The population in this study were all employees at PT. Ekaputra Prada Indonesia in Pekanbaru totaling 45 people, using Multiple Linear Regression. In this study, the sampling method used the Census Technique, which is a sampling technique in which the entire population is selected to be a member of the sample so that the sample becomes 45 respondents. The results in this study Seiri, Seiton, Seiso, Seiketsu and Shitsuke have a significant effect on Work Productivity. With the maintenance of space and better organization of the workplace, it will be able to increase company profits and also enable companies to show potential strengths and abilities so that the implementation of 5S will provide an increase in work productivity. Keywords: Seiri, Seiton, Seiso, Seiketsu, Shitsuke and Work Productivity